Accuracy of Potential Evapotranspiration Models in Different Time Scales - Aparecido, Lucas Eduardo De Oliveira; Meneses, Kamila Cunha De [UNESP]; Torsoni, Guilherme Botega; Moraes, José Reinaldo Da Silva Cabral De; Mesquita, Daniel Zimmermann (Sociedade Brasileira de Meteorologia, 2020)
Know the precision of potential evapotranspiration models in different agronomic and climatic conditions is useful for irrigated agriculture. Therefore, we aimed to compare 18 methods of estimation of ETP with the Penman-Monteith (FAO-56) method, at different time scales for the State of Mato Grosso do Sul. Time series of climatic data were used on a daily scale between 1983 and 2018 from 22 locations in the state of Mato Grosso do Sul. ETP estimation models tested were: Benevidez-Lopez, Blaney-Criddle, Camargo, Hamon, Hargreaves, Hargreaves-Samani, Jensen-Haise, Jobson, Kharrufa, Linacre, Makkink, Penman, Priestley-Taylor, Radiation, Romanenko, Tanner-Pelton, Thornthwaite, and Turc. These models were compared with Penman-Monteith in daily, weekly, and monthly scales. The comparison between the ETP estimation models and the Penman-Monteith model was performed by the statistical indices: accuracy (MAPE) and precision (R2aj). Estimation methods showed differences in efficiency over time scales. The best performances of the models were on the daily scale. For daily scale, methods of Priestley-Taylor, Hargreaves, Hamon, and Makkink present the best values of accuracy and precision for the State of Mato Grosso do Sul. In the weekly scale, the most accurate methods are Hamon and Makkink, while for monthly scale the best methods are Makkink and Priestley-Taylor.

Conhecer a precisão dos modelos de evapotranspiração potencial em diferentes condições agronômicas e climáticas é útil para a agricultura irrigada. Portanto, objetivou-se comparar 18 métodos de estimativa de ETP com o método de Penman-Monteith (FAO-56), em diferentes escalas de tempo para o Estado de Mato Grosso do Sul. Foram utilizadas séries históricas dos dados climáticos em escala diária entre 1983 a 2018 de 22 localidades no estado do Mato Grosso do Sul. Os modelos de estimativa de ETP testados foram: Benevidez-Lopez, Blaney-Criddle, Camargo, Hamon, Hargreaves, Hargreaves-Samani, Jensen-Haise, Jobson, Kharrufa, Linacre, Makkink, Penman, Priestley-Taylor, Radiation, Romanenko, Tanner-Pelton, Thornthwaite e Turc. Esses modelos foram comparados com Penman-Monteith em escalas diárias, semanais e mensais. A comparação entre os modelos de estimativa de ETP e o modelo de Pernman-Monteith foi realizada pelos índices estatísticos: acurácia (MAPE) e precisão (R2aj). Os métodos de estimativa demonstraram diferenças na eficiência em relação às escalas de tempo. Os melhores desempenhos dos modelos foram na escala diária. Para escala diária, os métodos de Priestley-Taylor, Hargreaves, Hamon e Makkink apresentam os melhores valores de acurácia e precisão para o Estado de Mato Grosso do Sul. Para escala semanal os melhores métodos são Hamon e Makkink, enquanto para escala mensal os melhores métodos para estimar a ETP são Makkink e Priestley-Taylor.
Acurácia de Modelos de Evapotranspiração Potencial em Diferentes Escalas de Tempo
Keywords: estimation methods; accuracy; precision; Penman-Monteith; water evaporation; métodos de estimativa; acurácia; precisão; Penman-Monteith; evaporação da água